PELAKSANAAN PUTUSAN ARBITRASE DI INDONESIA - Hulman Panjaitan (to-ra, 2018)
Abstract Dispute resolution through arbitration has many bene ts, so that the parties prefer to settle their dispute through an arbitration body compared to general justice which requires a long time and relatively large costs. Encouraged by this awareness and future preparations, the Indonesian government has issued Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. This law has regulated how the proceedings before arbitration and the procedure for implementing the award, both national and international in nature. Keywords: arbitration; Indonesian government; UU No. 30 Tahun 1999; regulation.